Analytic solution for transient responses of viscoelastic FG plates subjected to various asymmetrically loads. Issue 4 (4th July 2021) - Alavi, Seyed Hashem; Eipakchi, Hamidreza
Abstract: Due to the lightweight, flexibility, structural damping, and other superior properties, the viscoelastic functionally graded material (VFGM) are very effective in controlling and reducing vibration responses. With the technology developed, the theory of viscoelasticity has become one of the important branches in solid mechanics. This work aims to analyze the transient response of VFGM annular and sector plates subjected to the circumferentially distributed load using the first-order shear deformation theory. The Zener three-parameter model is adopted for the viscoelastic behavior of the plate to be viscoelastic in shear and elastic in bulk. The FG property of the plate is considered to vary through the thickness according to a power-law function in terms of the volume fractions of the constituents. Hamilton's principle is utilized to derive governing equations. The equations of motion are analytically solved using the perturbation technique and the Fourier series. Since the convergence rate of the present solution is very fast, several parametric studies are conducted on different geometrical and mechanical parameters. The validity and accuracy of the detailed results are compared with the finite element package. The results showed that the maximum lateral deflection in the VFGM plate is less than the other ones except for the ceramic plate. Besides, a decrease in gradient-index leads to that the effect of viscoelasticity appears in a shorter time.